THE EFFECT OF VILLAGE FUND PLANNING, IMPLEMENTATION, AND REPORTING ON GOOD GOVERNANCE WITH FINANCIAL PERFORMANCE AS A MODERATING VARIABLE - Vira Herianti; Paulina Yuritha Amtiran; Moni W. Muskanan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study investigates the effect of village fund planning, implementation, and reporting on good governance, with financial performance as a moderating variable in 20 villages across five sub-districts of South Central Timor Regency, East Nusa Tenggara Province, Indonesia. Using an explanatory quantitative approach, data were collected from 100 respondents comprising village heads, secretaries, finance officers, Village Consultative Body (BPD) members, and community representatives. Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS was employed for analysis. The results indicate that village fund implementation has a significant positive effect on good governance (β = 0.207, p = 0.043), while village fund planning (β = 0.115, p = 0.294) and reporting (β = 0.207, p = 0.092) do not. Financial performance significantly moderates the relationship between implementation and good governance (β = 0.220, p = 0.024), but does not moderate the planning–good governance or reporting–good governance relationships. These findings highlight that the quality of program execution and sound financial management are the primary determinants of good governance in village fund administration, with implications for capacity-building and accountability frameworks in rural public administration.